Do Children With Constipation Have Increased Risk of Asthma? Real-World Data From a Nationwide Population-Based Cohort Study - Huang, Yen-Chu; Wu, Meng-Che; Wang, Yu-Hsun; Wei, James Cheng-Chung (Frontiers in Pediatrics, 2021)
Background Asthma is one of the most burdensome childhood disorders. Growing evidence disclose intestinal dysbiosis may contribute to asthma via the gut-lung axis. Constipation can lead to alteration of the gut microbiota. The clinical impact of constipation on asthma has not been researched. Therefore, we aim to assess whether pediatric constipation influence the risk of developing asthma by a nationwide population-based cohort study. Methods We analyzed 10363 constipated patients and 10363 individuals without constipation between 1999 and 2013 from Taiwan’s National Health Insurance Research Database. Analysis of propensity score was utilized to match age, sex, comorbidities, and medications at a ratio of 1:1. In addition, multiple Cox regression analysis was performed to evaluate the adjusted hazard ratio of asthma. Furthermore, sensitivity tests and a stratified analysis were performed. Results After adjustment for age, sex, comorbidities, and medications, constipated patients had a 2.36-fold greater risk of asthma compared to those without constipation (adjusted hazard ratio [aHR]: 2.36, 95% C.I. 2.04-2.73, p<0.001). Furthermore, the severity of constipation is associated with an increased risk of asthma; the adjusted hazard ratio was 2.25, 2.85, and 3.44 within < 3 times, 3-12 times, and ≥12 times of laxatives prescription within one year, respectively. (p<0.001) Conclusion Constipation was correlated with a significantly increased risk of asthma. Pediatricians should be aware of the possibility of asthma in constipated patients. Further research is warranted to investigate the possible pathological mechanisms of this association.